The Interplay of Host Microbiota and Parasitic Protozoans at Mucosal Interfaces: Implications for the Outcomes of Infections and Diseases. - Ann-Katrein Bär; Niha Phukan; Jully Pinheiro; Augusto Simoes-Barbosa (PLoS Neglected Tropical Diseases)
Infections by parasitic protozoans are largely neglected, despite threatening millions of people, particularly in developing countries. With descriptions of the microbiota in humans, a new frontier of investigation is developing to decipher the complexity of host-parasite-microbiota relationships, instead of the classic reductionist approach, which considers host-parasite in isolation. Here, we review with specific examples the potential roles that the resident microbiota can play at mucosal interfaces in the transmission of parasitic protozoans and in the progress of infection and disease. Although the mechanisms underlying these relationships remain poorly understood, some examples provide compelling evidence that specific components of the microbiota can potentially alter the outcomes of parasitic infections and diseases in humans. Most findings suggest a protective role of the microbiota, which might lead to exploratory research comprising microbiota-based interventions to prevent and treat protozoal infections in the future. However, these infections are often accompanied by an unbalanced microbiota and, in some specific cases, apparently, these bacteria may contribute synergistically to disease progression. Taken together, these findings provide a different perspective on the ecological nature of protozoal infections. This review focuses attention on the importance of considering polymicrobial associations, i.e., parasitic protozoans and the host microbiota, for understanding these human infections in their natural microbial context.